What Can Long Terminal Repeats Tell Us About the Age of LTR Retrotransposons, Gene Conversion and Ectopic Recombination? - Jedlicka, Pavel; Lexa, Matej; Kejnovsky, Eduard (Frontiers in Plant Science, 2020)
LTR retrotransposons constitute a significant part of plant genomes and their evolutionary dynamics play an important role in genome size changes. Current methods of LTR retrotransposon age estimation are based only on LTR (long terminal repeat) divergence. This has prompted us to analyse sequence similarity of LTRs in 25,144 LTR retrotransposons from fifteen plant species. as well as formation of solo LTRs. We found that approximately one fourth of nested retrotransposons showed a higher LTR divergence than the pre-existing retrotransposons into which they had been inserted. Moreover, LTR similarity was correlated with LTR length. We propose that gene conversion can contribute to this phenomenon. Gene conversion prediction in LTRs showed potential converted regions in 25 % of LTR pairs. Gene conversion was higher in species with smaller genomes while the proportion of solo LTRs did not change with genome size in analyzed species. The negative correlation between the extent of gene conversion and the abundance of solo LTRs suggests interference between gene conversion and ectopic recombination. Since such phenomena limit the traditional methods of LTR retrotransposon age estimation, we recommend an improved approach based on the exclusion of regions affected by gene conversion.